2016
DOI: 10.15252/emmm.201606184
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ signaling directs serrated adenomas to the mesenchymal colorectal cancer subtype

Abstract: The heterogeneous nature of colorectal cancer (CRC) complicates prognosis and is suggested to be a determining factor in the efficacy of adjuvant therapy for individual patients. Based on gene expression profiling, CRC is currently classified into four consensus molecular subtypes (CMSs), characterized by specific biological programs, thus suggesting the existence of unifying developmental drivers for each CMS. Using human organoid cultures, we investigated the role of such developmental drivers at the premali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 67 publications
4
126
0
2
Order By: Relevance
“…In an interesting follow-up study, 146 cells in tubular adenomas that progressed to classic CRCs underwent apoptosis in response to TGF- β , consistent with its role in suppressing tumor growth, whereas a subgroup of sessile serrated adenomas progressed to subtype 4–like CRCs, with activation of genes in the TGF- β pathway. Expressing the BRAF v600E mutant in tubular adenoma organoids through CRISPR/Cas9 gene editing, mimicking the sessile serrated adenoma pathway in CRC, changed the response to TGF- β from apoptosis to the EMT.…”
Section: Future Directionsmentioning
confidence: 80%
“…In an interesting follow-up study, 146 cells in tubular adenomas that progressed to classic CRCs underwent apoptosis in response to TGF- β , consistent with its role in suppressing tumor growth, whereas a subgroup of sessile serrated adenomas progressed to subtype 4–like CRCs, with activation of genes in the TGF- β pathway. Expressing the BRAF v600E mutant in tubular adenoma organoids through CRISPR/Cas9 gene editing, mimicking the sessile serrated adenoma pathway in CRC, changed the response to TGF- β from apoptosis to the EMT.…”
Section: Future Directionsmentioning
confidence: 80%
“…Se ha reportado que los tumores CMS2 se originan a partir de adenomas tubulares, cuya progresión adenoma-carcinoma es iniciada por el gen supresor de tumores APC con una alta actividad en la vía de señalización intracelular Wnt/MYC 35,41 . Si bien no contamos con perfiles moleculares que den cuenta de la activación de la vía Wnt/MYC, logramos establecer que los tumores categorizados CMS2 se asocian a mutaciones en oncogenes como KRAS y PI3KCA y poseen características clínicas asociadas a una mejor respuesta a terapias asociadas a la vía CIN-alta.…”
Section: Discussionunclassified
“…Los tumores CMS4 se han descrito como el subtipo de peor pronóstico 19,33 . Estos tumores provienen de pólipos sésiles aserrados, pero a diferencia del subtipo CMS1, presentan sobreexpresión de señales asociadas a la activación del factor de crecimiento transformante (TGF-β) que desencadena señales intracelulares asociadas a la transición epitelio-mesénquima (MET) 35,41 . Según nuestros datos, al momento del diagnóstico, la mayor prevalencia de tumores en estados avanzados fueron categorizados en CMS2 y CMS4.…”
Section: Discussionunclassified
“…However, the same group later showed that Apc mutations are not always required to reveal the oncogenic capacity of deregulated Tgf-β signalling, as mice with mutant Kras (Kras G12D ) and deletion of Tgfbr2 specifically in the intestine also developed intestinal tumours with ~15% of them becoming invasive and metastasising to the lymph nodes and/or lungs (72). This is of interest to human CRC as many tumours that have mismatch repair deficiency (approximately 20%) do not mutate APC and have mutations in TGFBR2 (due to a microsatellite repeat which is commonly mutated) TGF-β has very recently also been identified as a regulator of the serrated neoplasia pathway in the intestine (73). Colon cancer is currently classified into four consensus molecular subtypes (CMSs) according to several biological parameters including gene expression and molecular aberrations (74).…”
Section: Interaction Of Oncogenes and Tumour Suppressor Genes In Intementioning
confidence: 99%
“…Colon cancer is currently classified into four consensus molecular subtypes (CMSs) according to several biological parameters including gene expression and molecular aberrations (74). Work from JP Mademas lab showed that sessile serrated adenoma organoids carrying BRAF V600E mutations respond differently from tubular adenoma organoids when exposed to TGF-β, and acquired a mesenchymal phenotype, characteristic of the CMS4 group which has a very poor clinical prognosis (73). Indeed work from Eduard Batlle's group suggests that these mesenchymal expression patterns in serrated tumours are due to TGF-β ligand secretion from the stroma, and these may confer the poor prognosis of this subtype, (75) suggesting that TGFβ inhibition in this group may be a therapeutic strategy (75).…”
Section: Interaction Of Oncogenes and Tumour Suppressor Genes In Intementioning
confidence: 99%